PERAN TEKNOLOGI DALAM PEMBELAJARAN PAUD - Nur Rochmah Setianingrum; Ni Kadek Aris Rahmadani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the role of technology in early childhood education (ECE),focusing on its benefits, challenges, and applications in the learning process. Asystematic literature review (SLR) of ten primary studies published between 2019and 2025 was conducted. The findings reveal that technology improves children’smotivation, creativity, and understanding of abstract concepts. Tools such asAugmented Reality (AR), interactive multimedia, and digital educationalapplications enhance learning experiences, making them more engaging andpersonalized. However, challenges such as teachers’ low digital literacy, limitedinfrastructure access, and concerns about excessive screen time remainsignificant obstacles. Effective technology integration in ECE requires a balancedand well-planned approach involving collaboration among educators, parents, andpolicymakers. Training for teachers and supportive policies are essential tomaximize technology’s potential in fostering holistic child development.